Association between delirium, adverse clinical events and functional outcomes in older patients admitted to rehabilitation settings after a hip fracture: A multicenter retrospective cohort study. Issue 5 (20th February 2019) - Morandi, Alessandro; Mazzone, Andrea; Bernardini, Bruno; Suardi, Teresa; Prina, Roberto; Pozzi, Christian; Gentile, Simona; Trabucchi, Marco; Bellelli, Giuseppe
Abstract : Aim: The aim of the present study is to investigate how delirium and adverse clinical events (ACE) contribute independently and in combination to functional outcomes in older patients admitted to rehabilitation settings after a hip fracture. Methods: This is a multicenter retrospective cohort study of patients aged ≥65 years admitted after hip fracture surgical repair to three Italian rehabilitation units. Delirium on admission was evaluated with the Confusion Assessment Method. ACE during the rehabilitation stay were recorded, including infections (i.e. urinary tract infections, other infections), non‐infectious ACE (i.e. cardiovascular events, respiratory failure, pulmonary embolism) and falls. A multivariable linear regression was used to evaluate the effect of ACE and delirium on functional outcome, adjusting for covariates determined a priori. Results: A total of 519 patients were included in the study. The mean ± SD age was 82.9 ± 9.4 years. ACE occurred in 277 patients (53.4%), delirium alone was present in 19 patients (3.6%). Both conditions were present in 58 patients (11.2%). Compared with patients without delirium or ACE, those with ACE or delirium were more likely to have a worse functional outcome (−6.7 Barthel Index points [−11.6; −1.7]; P = 0.008; −13.2 [−25.6; −0.8]; P = 0.038) at discharge, and patients with both conditions had an even lower Barthel Index score (−18.6 Barthel Index points [−26.9; −10.3]; P < 0.001). Conclusions: ACE and delirium are very common in older patients admitted to rehabilitation settings after hip fracture, and frequently coexist. As both ACE and delirium could impact on functional outcome, alone and in combination, a clinical geriatric approach is necessary for this population to minimize risks.Geriatr Gerontol Int 2019; 19: 404–408 .